Process Optimization of Sorghum Based Extruded Snack Incorporated with Tilapia (Oreochromis niloticus) Meat using RSM - George, Cibia; C. N. Ravishankar; Joshy C. G; Sreejith S (Fishery Technology, 2022)
A study was carried out to optimize processing condition for developing an acceptable Ready to Eat extruded snack using Response Surface Methodology. Tilapia mince was incorporated with a composite blend of sorghum grits and corn flour as base material was used for this study. The mild flavoured and protein rich Tilapia, a rich source of omega 3 fatty acids was used to develop an acceptable ready to eat extruded snack using Response surface methodology. The snack was prepared with a twin-screw extruder using composite flour mixture of Sorghum (40-70%) and corn (20-40%) with tilapia fish mince (10-20%). The effect of independent variables such as temperature (120-1300 C), screw speed (300-400 rpm) on dependant variables such as bulk density, expansion ratio, hardness, specific mechanical energy was analysed. Mixture response design with 27 trials were carried out to study optimisation of physical parameters and found that Sorghum 44.87%, corn 40%, tilapia mince 15.13%, at 1300 C and 343 rpm screw speed was found to be ideal for the expanded extruded snack with bulk density 0.132, expansion ratio 3.5, hardness 637.52, specific mechanical energy 165.41, colour 69.58(L*), 1.29 (a*), 18.58 (b*) respectively. The values pertaining to the product were statistically significant with R2 value >85 was obtained, for all models. The study explores the possibility of utilization of low-cost underutilised Sorghum and freshwater fish Tilapia in product development with improved nutritional quality, using response surface methodology